MEDIA NYANYIAN DALAM PENGUASAAN KOSA KATA BARU BAHASA ARAB PADA SISWA KELAS RENDAH MADRASAH IBTIDAYAH - Ahmad Fauzan Ilmi (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2020)
This research aims to describe a fun teaching medium in mastering the new Arabic vocabulary in Madrasah Ibtidaiyah, Arabic media based on this song aimed at making it easier for low-grade students of Madrasah Ibtidaiyah to master new vocabulary in Arabic learning. The transition period from kindergarten to elementary school sitting in madrasah ibtidaiyah benches often shocks students with a much different new atmosphere when they are still sitting in kindergarten where the learning process uses more singing and playing. This research is qualitative descriptive research by descriptive of phenomena that occur in the process of learning Arabic. Data obtained through observations, interviews, and library studies. The result of this study is that students are more confident and active in learning mastery of new vocabulary, they feel happier and faster in remembering new vocabulary. The same main problem in Arabic learning in the lower classes of Madrasah Ibtidaiyah, namely that the average student is still many who have not been able to read Arabic writing, thus causing learning in the classroom to be hampered. One solution offered is singing-based Arabic language learning media. Keywords: Singing media, mastery of Arabic vocabulary, madrasah low class